Association between Pre-pregnant Overweight and Obesity and Periodontal Disease during Pregnancy: A Cross Sectional Study (International Journal of Studies in Nursing, 2017)
Background: Obesity is considered а noteworthy public health issue in both developed & developing countries. Among the 1.5 billion overweight individuals worldwide, 300 million of them were obese women. In the general, the prevalence of maternal obesity has increased 60% in the previous two decades with nearly 1 in 3 women now entering pregnancy obese. Also, the periodontаl disease has been observed to be prevalent in pregnant women with the prevalence ranging from 20% to more than 50%, especially economically disadvantaged women. Aim: explore the relation between pre-pregnant overweight and obesity with periodontal disease during pregnancy. Subjects & Methods: cross-sectional study among 400 pregnant women were booked in the high-risk obstetric departments and the antenatal outpatient clinics at governmental general hospitals in El-Fayoum City and governmental university hospital in El-Mansoura city. Results: The mean age of pregnant women was 29.9 ± 6.2 with increase the prevalence of periodontal disease in pregnant women (83.5%). Statistically significant correlation was found between prenatal weight and periodontаl disease during pregnancy (p ≤ 0.0001) with increasing the prevalence of periodontal disease in prenatal obese women (53.2%) and over weight (39.7%) were observed in women who were in their 3rd trimester (р = 0.011). Increase prevalence of periodontal with poor oral hygiene and sedentary activity. Conclusion: increased pre-pregnancy obesity & overweight are positively correlated with periodontal disease prevalence among pregnant women, and Pregnancy itself may also be associated with аn increased risk of periodontal disease. Recommendations: Activating the role of the maternity and community health nurse in branches of Obstetrics and antenatal clinics to enhance pregnant women's knowledge regarding oral health risks of obesity & overweight.